Organoleptical and instrumental examination of broilers’ valuable meat-parts - Holcvart, Mária; Elek, Sándor; Hódi, Katalin (Acta Agraria Debreceniensis, 2012)
The aim of our study was to compare some meat quality parameters (color,- evenness of colour- and tone of meat) of Ross 308, Cobb 500 and Ross parents hibrids. These qualities are of preliminary importance for consumers and are related to several evaluating features influencing the preparation. The colour of the breast and thigh muscles was measured by Minolta CR-300 type colour measuring equipment. The evenness of color- and tone of the breast and thigh muscles were measured in the laboratory of Campden BRI Magyarország Nonprofit Kft.We found that in the females the color of Ross 308 pullets’ breast meat was significantly darker. In the males the darkest breast meat was detectable in the case of the Ross parents hybrids. In neither sexes wast found significant difference – in all but one – in quality parameters of thigh meat.